2014
DOI: 10.21608/jfds.2014.53212
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Sweet Whey in Production of Whey Guava Beverages.

Abstract: Whey and juice of guava (Pisdium guajava) were utilized at various combinations (85:15, 80:20, 75:25 and 70:30) for preparation of nutritious beverages and evaluated for various chemicals, microbial and sensory attributes during storage. The study revealed that the beverage prepared with 75% whey and 25% guava juice scored maximum for almost all sensorial quality attributes such as appearance, color, flavor, taste and over all acceptability. As well as the juice was high content of ascorbic acid (18.87mg/100g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
4
3
0
Order By: Relevance
“…The obtained results indicated that sweet whey has pH value of 5.56 and contains 6.4 % total solids, 5.7 % total soluble solids, 0.20 % fat,0.9 % protein, 4.80 % lactose, and 0.50 % ash. The current results are in general agreement with those reported by Ragab et al (2010), and Yonis et al (2014). As shown in Table 2, cactus pear fruit juice contains 17.31 % total solids, 10.50 % total soluble solids, 0.50 % fat, 0.96 % protein, and 0.65 % ash while kaki juice contains 22.85 % total solids, 14.10 % total soluble solids, 0.18 % fat, 0.57 % protein, 18.16 % and 0.34 % ash.…”
Section: Chemical Composition Of Sweet Whey and Fruit Juicessupporting
confidence: 94%
See 1 more Smart Citation
“…The obtained results indicated that sweet whey has pH value of 5.56 and contains 6.4 % total solids, 5.7 % total soluble solids, 0.20 % fat,0.9 % protein, 4.80 % lactose, and 0.50 % ash. The current results are in general agreement with those reported by Ragab et al (2010), and Yonis et al (2014). As shown in Table 2, cactus pear fruit juice contains 17.31 % total solids, 10.50 % total soluble solids, 0.50 % fat, 0.96 % protein, and 0.65 % ash while kaki juice contains 22.85 % total solids, 14.10 % total soluble solids, 0.18 % fat, 0.57 % protein, 18.16 % and 0.34 % ash.…”
Section: Chemical Composition Of Sweet Whey and Fruit Juicessupporting
confidence: 94%
“…etc. (Gad et al, 2013, Yonis et al, 2014, Chavan et al, 2015. However, other fruits like cactus pear and kaki, despite its nutritional importance, are not used until now in preparation of such beverages.…”
Section: Introductionmentioning
confidence: 99%
“…With storage, differences between the TPC of sample-1, sample-2, and sample-3 increased significantly (p < 0.05), while samples between themselves did not show any significant differences in the TPC under study on the 5th, 10th, 20th, and 25th day of refrigerated storage. The TPC of the prepared whey-mango based beverage mixed in the current study is consistent with the findings of Gorachiya [79], Sharma et al [80], Mohamed et al [68], Yonis et al [81], and Ismail et al [82], who reported a similar trend of significant increase (p < 0.01) in the TPC of whey-based beverages with an increase of storage period. Whey contains lactose sugar and proteins, which may be conducive to the growth of microorganisms during storage [83].…”
Section: Microbiological Analysissupporting
confidence: 92%
“…Ismail et al, (2011) studied the microbial and chemical evaluation of whey based mango beverage and reported that standard plate count significantly increased with increase of storage of whey based mango beverage. Similar results was obtained by Yonis et al, (2014) who studied the utilization of sweet whey in production of whey guava beverages and observed significant increase in the standard plate count with increase of storage period. The coliform count was not observed at day 0 and 3 in sample T 0 , T 1 and T 2 , respectively.…”
Section: Microbial Analysissupporting
confidence: 87%